PM2.5 and PM10: The influence of sugarcane burning on potential cancer risk - Silva, Flavio S. [UNESP]; Cristale, Joyce [UNESP]; Andre, Paulo A.; Saldiva, Paulo H. N.; Marchi, Mary Rosa Rodrigues de [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
In Brazil, sugarcane fields are often burned to facilitate manual harvesting, and this burning causes environmental pollution from the large amounts of soot released into the atmosphere. This material contains numerous organic compounds such as PAHs. In this study, the concentrations of PAHs in two particulate-matter fractions (PM2.5 and PM10) in the city of Araraquara (SE Brazil, with around 200,000 inhabitants and surrounded by sugarcane plantations) were determined during the sugarcane harvest (HV) and non-harvest (NHV) seasons in 2008 and 2009. The sampling strategy included four campaigns, with 60 samples in the NHV season and 220 samples in the HV season. The PM2.5 and PM10 fractions were collected using a dichotomous sampler (10 L min(-1), 24 h) with Teflon (TM) filters. The filter sets were extracted (ultrasonic bath with hexane/acetone (1:1 v/v)) and analyzed by HPLC/Fluorescence. The median concentration for total PAHs (PM2.5 in 2009) was 0.99 ng m(-3) (NHV) and 3.3 ng m(-3) (HV). In the HV season, the total concentration of carcinogenic PAHs (benz(a)anthracene, benzo(b)fluoranthene, benzo(k)fluoranthene, and benzo(a)pyrene) was 5 times higher than in the NHV season. B(a)P median concentrations were 0.017 ng m(-3) and 0.12 ng m(-3) for the NHV and HV seasons, respectively. The potential cancer risk associated with exposure through inhalation of these compounds was estimated based on the benzo[a]pyrene toxic equivalence (BaPeq), where the overall toxicity of a PAR mixture is defined by the concentration of each compound multiplied by its relative toxic equivalence factor (TEF). BaPeq median (2008 and 2009 years) ranged between 0.65 and 1.0 ng m(-3) and 1.2-1.4 ng m(-3) for the NHV and HV seasons, respectively. Considering that the maximum permissible BaPeq in ambient air is 1 ng m(-3), related to the increased carcinogenic risk, our data suggest that the level of human exposure to PAHs in cities surrounded by sugarcane crops where the burning process is used is cause for concern. (C) 2010 Published by Elsevier Ltd.
Keywords: Polycyclic aromatic hydrocarbons (PAHs); benzo[a]pyrene toxic equivalence; Biomass burning; Cluster analysis; Principal components analysis